In-Vitro Evaluation Of Pectin As A Compression Coating Material For Colon Targeted Drug Delivery - NITESH SHAH; TEJAL SHAH; AVANI AMIN (International Journal of Pharma and Bio Sciences, 2011)
Colon targeted delivery of satranidazole (STZ), which immediately releases the drug as soon as the drug delivery system reaches the colon was formulated. Different grades of pectin were used as a compression coat and the effect of degree of esterification (DE) of pectin on swelling and drug release property was evaluated. STZ is a sparingly soluble drug, so to obtain maximum effect of drug at the site of action the solubility enhancement was carried out using Hydroxypropyl-β-cyclodextrin (HP-β-CD). Pectin as a compression coat was unable to direct STZ containing core tablets to the colon, so HPMC was added to increase the tensile strength of the coat. STZ core tablets compression coated with High DE pectin: HPMC in 1:1 ratio imparted the lag time of 5 h and burst release in colon.